DNMT3A mutations are associated with inferior overall and leukemia‐free survival in chronic myelomonocytic leukemia. Issue 1 (7th December 2016) - Patnaik, Mrinal M.; Barraco, Daniela; Lasho, Terra L.; Finke, Christy M.; Hanson, Curtis A.; Ketterling, Rhett P.; Gangat, Naseema; Tefferi, Ayalew
Abstract : DNMT3A mutations are seen in ∼5% of patients with chronic myelomonocytic leukemia (CMML) and thus far, have had an indeterminate prognostic impact on survival. We carried out this study to assess the prognostic impact of DNMT3A mutations on a larger informative cohort of CMML patients ( n  =   261). DNMT3A mutations were seen in 6% ( n  =   16); 56% ( n  =   9) male, with a median age of 64 years. Eighty‐one % of DNMT3A mutations were missense, with the Arg882 mutational hot spot accounting for 63% of all changes. Five (31%) patients had an abnormal karyotype whereas concurrent gene mutations ( SF3B1/SRSF2/U2AF1 −56%, TET2 −50%, and ASXL1 −25%) were seen in all patients. Apart from a higher frequency of SF3B1 ( P  = 0.0001) and PTPN11 ( P  = 0.005) mutations and a lower frequency of SRSF2 ( P  = 0.004) mutations, there were no significant differences between DNMT3A mutated patients and their wildtype counterparts. In univariate analysis, survival was shorter in DNMT3A mutated (median 8 months) versus wildtype (median 27 months) patients ( P  = 0.0007; HR 2.9, 95% CI 1.5–5.7); with other variables of significance including lower hemoglobin ( P  = 0.002), higher leukocyte count ( P  = 0.0009), higher monocyte count ( P  = 0.0012), circulating blast % ( P  = 0.001), circulating immature myeloid cells ( P  = 0.01), bone marrow blast % ( P  = 0.045), abnormal karyotype ( P  = 0.02), and ASXL1 ( P  = 0.01) mutations. In a multivariable model that included the aforementioned variables, when both DNMT3A and ASXL1 mutations were added, only DNMT3A ( P  < 0.0001) and ASXL1 ( P  = 0.004) mutations remained significant. DNMT3A mutations were also predictive of a shortened leukemia‐free survival. These findings warrant inclusion of DNMT3A mutations in molecularly integrated CMML prognostic models. Am. J. Hematol. 92:56–61, 2017. © 2016 Wiley Periodicals, Inc.